TREE SPECIES DIVERSITY, SOIL PHYSICOCHEMICAL, BIOMASS, CARBON STOCK AND CARBON DIOXIDE ASSESSMENT IN MUNGULVU GRAZING RESERVES MUBI-NORTH LGA, ADAMAWA STATE, NIGERIA - Umar, M.R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study evaluated the diversity of tree species, soil physicochemical properties, biomass, carbon stock, and carbon dioxide (CO₂) sequestration in the Mungulvu grazing reserve. A systematic line transect approach was adopted, consisting of two parallel transects, each 1500 m long and spaced 500 m apart. Along each transect, four sample plots of 50 × 50 m were established at 100 m intervals, given a total of eight plots. Within each plot, all living trees with a diameter at breast height (DBH) ≥10 cm were identified and measured for diameter at breast height, diameter at the base, middle, and top, as well as total height. Soil samples were collected at four depth intervals (0–15, 16–30, 31–45, and 46–60 cm) from three points per plot. Data were analysed using one-way analysis of variance (ANOVA) and Student’s t-test. A total of 11 tree species belonging to six families were recorded, with a density of 62 trees ha⁻¹ and dominance of the Phyllanthaceae and Fabaceae families. Diameter and height class distributions indicated a concentration of individuals in lower size classes. Total aboveground biomass, carbon stock, and CO₂ were estimated at 7.94 t ha⁻¹, 3.97 t ha⁻¹, and 14.56 kg, respectively. Soils were predominantly sandy, with moderate bulk density, porosity, and water-holding capacity. Chemical properties indicated a slightly acidic to near-neutral pH, low electrical conductivity, moderate organic matter content, and a moderate effective cation exchange capacity. The findings highlighted the importance of sustainable grazing and soil management practices to conserve biodiversity, enhance biomass and carbon storage, and maintain ecosystem stability in the Mungulvu grazing reserve.